2019
DOI: 10.1038/s41598-019-57010-9
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 exerts antiarrhythmic effects by inhibiting INa and ICaL in rabbit ventricular myocytes

Abstract: Ginsenoside Rb1 exerts its pharmacological action by regulating sodium, potassium and calcium ion channels in the membranes of nerve cells. These ion channels are also present in cardiomyocytes, but no studies have been reported to date regarding the effects of Rb1 on cardiac sodium currents (INa), L-type calcium currents (ICaL) and action potentials (APs). Additionally, the antiarrhythmic potential of Rb1 has not been assessed. In this study, we used a whole-cell patch clamp technique to assess the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A study found that ginsenoside Rg3 can change the electrocardiogram (ECG) and monophasic action potential (MAP) of Langendorff perfused rabbit heart, shorten the QT interval, and may be related to alleviating the current inhibition of human ether-related genes (hERG) and accelerating the activation process of potassium channels . Another study has shown that ginsenosides can also treat arrhythmias by inhibiting the voltage-dependent Na + current in the myocardium and reducing the amplitude of action potentials (Liu et al, 2019). These studies fully demonstrate the antiarrhythmic therapeutic potential of ginsenosides.…”
Section: Arrhythmiamentioning
confidence: 67%
“…A study found that ginsenoside Rg3 can change the electrocardiogram (ECG) and monophasic action potential (MAP) of Langendorff perfused rabbit heart, shorten the QT interval, and may be related to alleviating the current inhibition of human ether-related genes (hERG) and accelerating the activation process of potassium channels . Another study has shown that ginsenosides can also treat arrhythmias by inhibiting the voltage-dependent Na + current in the myocardium and reducing the amplitude of action potentials (Liu et al, 2019). These studies fully demonstrate the antiarrhythmic therapeutic potential of ginsenosides.…”
Section: Arrhythmiamentioning
confidence: 67%
“…GnRb1 is a glycoside from the class of triterpenoid saponins, found in Panax ginseng, that has a long history of being used in China to cure various ailments. Its main biopharmacological properties includes cardioprotective [ 26 , 27 ], neuroprotective [ 28 , 29 ], nephroprotective [ 30 ], immunoregulatory [ 31 ], and anti-inflammatory properties [ 15 , 32 , 33 ]. GnRb1 was proved to suppress LPS-induced ALI [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existing studies reported that RG can be used to treat coronary heart disease and atherosclerosis by reducing blood lipid levels and improving inflammation ( Hernández-García et al, 2019 ; Lu et al, 2019 ; Im, 2020 ). Additionally, it can inhibit arrhythmia by affecting the ion channels, such as activating potassium channel while blocking calcium channel and sodium current ( Liu Z. et al, 2019 ; Gou et al, 2020 ). Furthermore, by ameliorating mitochondrial function and reducing oxidative damage in cardiomyocytes, it can prevent ventricular remodeling and heart failure.…”
Section: Sfi -Basic Characteristics and History Of Usementioning
confidence: 99%